The National Security System of the Republic of Montenegro (Annual of the Faculty of Philosophy in Skopje, 2018)
The national security system of the Republic of Montenegro is based upon the specificsof the Montenegrin country and is adjusted in such a manner that is able to respondto the contemporary security challenges. That said, it has to address to a great extent thethreats and risks which the country faces on a national, regional and international plan.This signifies building an efficient system, functional and operative, for dealing with securitythreats to the country. The basic dilemmas which are subject of discussion in the paperitself refer to the issues “Whether the national security system could completely enforce thenational security policy?” as well as the question “Whether Montenegro, because of the limitedresources, has the adequate capacities for dealing with the security risks and threats?”These issues are always in the open row for which new answers are looked for.
Keywords: MONTENEGRO; SECURITY; SYSTEM; SECURITY SYSTEM; POLICY; SECURITY POLICY